1937
DOI: 10.1042/bj0311441
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of vitamin B1 in blood by a modification of Schopfer's test

Abstract: SCHOPFER [1935, 1] has described a method for estimating small amounts of vitamin B1 by means of its growth-promoting activity on a mould, Phycomyces Blakesleeanus. It has been found that this method, with some modifications, can be used as a comparatively simple test for vitamin B1 in small samples of blood. The method as modified for this purpose is here described. In the discussion that follows the quantitative validity of this test is considered. METHOD The medium. A series of 50 ml. conical flasks is prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1938
1938
1958
1958

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…By plotting the weight of mycelium obtained against the quantity of vitamin B, added, a smooth curve could be produced, and Schopfer used this as a quantitative test for vitamin B, in foodstuffs and animal tissues. We have employed Schopfer's technique and applied it to the THE BRITISH 879 NIEDICAL JOURNAL estimation of the vitamin B, content of human blood; our method is very similar to that since described by Meiklejohn (1937), details of which were kindly made available to us by Professor R. A. Peters. The test we used was as follows:…”
Section: Resultsmentioning
confidence: 99%
“…By plotting the weight of mycelium obtained against the quantity of vitamin B, added, a smooth curve could be produced, and Schopfer used this as a quantitative test for vitamin B, in foodstuffs and animal tissues. We have employed Schopfer's technique and applied it to the THE BRITISH 879 NIEDICAL JOURNAL estimation of the vitamin B, content of human blood; our method is very similar to that since described by Meiklejohn (1937), details of which were kindly made available to us by Professor R. A. Peters. The test we used was as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The glassware was Pyrex; it was rinsed with bichromate-sulphuric acid, washed thoroughly with hot water, distilled water (three times), and glass-distilled water. For experiments 7 to 11 the niacronutrients (i.e., the constituents of the basal medium) and the distilled water were tested with dithizone (Fischer 1934, 1937, Snell and Snell 1936, Stout and Arnon 1939, Sandell 1944, Feigl 1947. The test was carried out in the following way: 4 mg dithizone (diphenylthiocarhazone) were dissolved in 100 ml chloroform, and 0.2 ml of this solution were shaken vigourously with 2 ml of the solution to he tested in a small test tuhe (100 mmX9 mm, cuhic capacity ca.…”
Section: Methodsmentioning
confidence: 97%
“…In fact, the method and the substrate recommended by Schopfer for the Phycomyces assay on vitamin Bj has been employed successfully by a number of authors for a wide variety of natural substances (for literature references see Bang 1944 andSchopfer 1945). Meiklejohn (1937) found that it gave good results for blood, and claimed to have proved that substances present in blood other than vitamin Bd o not interfere. This was refuted by Sinclair (1938 and1939), who found that an adjuvant factors in hlood would interfere, most often giving too high values for vitamin Bj^.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…In the first application of a quantitative microbiological assay procedure to vitamin determination, Schopfer (1935a, b) described a method for the assay of thiamine using Phycomyces blakesleeanus as the test organism. Several investigators (Meiklejohn, 1937;Sinclair, 1938;Bonner and Erickson, 1938;Burkholder and McVeigh, 1940) modified and applied this method vith some success. The accuracy of the method has been confirmed by comparison with rat growth and thiochrome procedures (Hamner et al, 1943).…”
Section: Types Of Gravimetric Methodsmentioning
confidence: 99%
“…The nitrogen metabolism of the test organisms may be a source of difficulty in gravimetric assays. For example, the response of Phycomyces blakesleeanus to thiamin will vary with both the concentration and source of nitrogen (Meiklejohn, 1937;Sinclair, 1938;Burkholder and McVeigh, 1940) (table 1). Further, if a single source of nitrogen, such as asparagine, is utilized in the basal medium at its apparent optimum concentration, nitrogenous constituents of complex biological samples may stimulate additional growth of this organism (Sinclair, 1938).…”
Section: Factors Which Influence Gravimetric Methodsmentioning
confidence: 99%